PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PENDIDIKAN KARAKTER DAN DAMPAKNYA KEPADA PRESTASI PESERTA DIDIK - WELNITA WELNITA (ABDUSSALAM: Jurnal Pendidikan Dan Kebudayaan Islam, 2025)
This study examines the role of Islamic Religious Education (PAI) teachers in character education and its impact on student achievement at SDN 01 Pasar Kubang. The primary issue lies in the gap between the theoretical ideals of character education and its practical implementation, as observed in the school’s inconsistent student discipline and moral behavior despite existing religious programs. The research aims to: 1) analyze the role of PAI teachers in instilling character values, 2) identify the influence of character education on student achievement, and 3) recommend effective character-based PAI teaching strategies. Using a qualitative descriptive approach, data were collected through semi-structured interviews, participatory observation, and document analysis, then analyzed via the Miles & Huberman interactive model. Findings reveal that PAI teachers act as role models and facilitators, integrating character values through dynamic methods like group discussions and simulations, which enhance students’ academic and non-academic performance. Supportive factors include school policies and parental collaboration, while constraints involve curriculum limitations and varied student backgrounds. The study concludes that holistic character education, aligned with Islamic principles and social constructivism, significantly boosts student achievement. Recommendations include longitudinal studies and mixed-method approaches for future research.